PENGEMBANGAN E-MODUL KONSTRUKSI DAN UTILITAS GEDUNG BERBASIS PROYEK PADA KOMPETENSI KEAHLIAN DESAIN PEMODELAN DAN INFORMASI BANGUNAN (DPIB) DI SMK - Lutfiah Sungkar; Riyan Arthur; Anisah Anisah (Jurnal Pendidikan Teknik Bangunan, 2023)
This research is a development research that aims to produce project-based e-modules for detailed images of columns and beams in the Building Construction and Utilities subject. The research method used is Research and Development (RD) using a model that refers to the ADDIE research and development model, namely analysis, design, development, implementation, and evaluation. The development of this e-module is limited to the development stage. This study uses a questionnaire instrument to collect product due diligence data through validation tests by media experts and material experts, as well as test instruments in the form of pretest and posttest to collect product trial data for class XI DPIB students at SMKN 1 Kemang Bogor. Expert validation data analysis uses the average score formula and product trials use the normalized gain formula. The results of the development of teaching materials in the form of project-based e-modules detailed drawing material for columns and beams in the Building Construction and Utilities subject. The validation results by media experts obtained an eligibility percentage of 87.05% with the "Very Good" criteria. The results of the validation by material experts obtained an eligibility percentage of 85.69% with the "Very Good" criteria. The results of the small group trials obtained an N-Gain value of 0.3 with the "Medium" criteria. The results of the field trials obtained an N-Gain value of 0.7 with the "High" criteria.